SOCIAL SUPPORT OF PARENTS OF CHILDREN WITH LEUKEMIA - Nursyamsiyah Nursyamsiyah (Belitung Raya Foundation, Indonesia, 2019)
Background: Leukemia in children is not only a stressor for children but also all family members, especially for parents. Caring for children with leukemia relies on the importance of social support to overcome various crises caused by the disease and its treatment. However, parents' perceptions of social support can be affected by several factors. Thus, assessment of factors that impact social support of parents of children with leukemia is needed. Objective: This study aimed to analyze the social support perceived by parents of children with leukemia and examine the relationship between perceived social support and characteristics of parents and children. Methods: A quantitative study with cross-sectional approach in 104 parents of children with leukemia aged 3-18 years. Social support was measured using Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire. Data were analyzed using univariate analysis, Mann-Whitney U, Kruskal-Wallis, and Spearman Test. Results: Total scale score of the Multidimensional Scale of Perceived Social Support (MSPSS) of parents of children with leukemia was 5.74 ± 0.48. The highest subscale score was on family support (6.06 ± 0.46). There were statistically significant differences in MSPSS total scores based on parental education and family income (p <0.05). Conclusion: Nurses play an important role to provide support for parents who have children with leukemia, especially in risky families. Support that nurses can provide among parents of children with leukemia is by giving information about disease and care, empowering the family, and finding support outside the family, such as the source of financial support related to treatment, utilization of cancer foundations, and supporting group and others.